Reactivity of p53 protein in canine transmissible venereal tumor - Moro, J.V. [UNESP]; Tinucci-Costa, M. [UNESP]; Silveira, A.C.T. [UNESP]; Gerardi, D.G. [UNESP]; Alessi, A.C. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2010)
A expressão da proteína p53 foi avaliada em espécimes de tumor venéreo transmissível canino (TVT) de ocorrência natural (n=8); resistente à quimioterapia (n=4) e transplantado em cão nas fases de progressão tumoral (n=8), de latência (n=8) e de regressão (n=8). Os espécimes foram submetidos à reação de imunoistoquímica. Os resultados mostraram porcentagem média de células imunomarcadas de 18,6% no TVT de ocorrência natural, de 23,8% no TVT refratário, 22,9% nos TVTs transplantados nas fases de progressão e latência e de 35,8% na fase de regressão. Os resultados sugerem que há uma anormalidade funcional no gene P53 e seus produtos nos tumores estudados, apesar de não ser possível correlacionar a porcentagem de células marcadas pelo p53 ao prognóstico.

The expression of p53 protein was evaluated in canine transmissible venereal tumor (CTVT), as following: natural occurrence (n=8); resistant to chemotherapy (n=4); and allogeneic transplanted in progression (n=8), stable (n=8), and regression (n=8)stages. The collected specimens were submitted to GM1 immunohistochemical reaction. Results showed a mean percentage of immunomarked cells around 18.6% in CTVT of natural occurrence, 23.8% in CTVT resistant to chemotherapy, 22.9% in allogeneic transplanted CTVT in both progression and stable stages, and 35.8% in transplanted CTVT in regression stage. The results suggest that there is a functional abnormality in p53 gene and its products in the studied tumors; although, it is not possible to correlate the percentage of cells marked by p53 and a prognosis.
Reatividade da proteína P53 no tumor venéreo transmissível canino
Keywords: Immunohistochemistry; p53; Oncology; transmissible venereal tumor; Cão; Imuno-histoquímica; p53; Oncologia; Tumor venéreo transmissível